A REVISION OF THE ANATOMY OF THE TRIASSIC PTEROSAUR AUSTRIADRACO DALLAVECCHIAI KELLNER, 2015 AND OF ITS DIAGNOSIS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2021)
Several skeletal elements preserved in the holotype and only specimen of the pterosaur Austriadraco dallavecchiai Kellner, 2015 (uppermost Triassic, Austria) have not been identified or have remained undescribed in previous works. They include important elements for the systematic and phylogenetic studies such as the femur, premaxillae and maxillary teeth. The broad bone initially considered the sternal plate is plausibly formed by the fused frontals, as already suggested by some authors. The diagnosis of Austriadraco dallavecchiai is amended on the basis of new information. The close relationship of Austriadraco dallavecchiai to Seazzadactylus venieri from the uppermost Triassic of Friuli (north-eastern Italy) is further supported by the morphological similarity between the two taxa (e.g. they share similar postorbital process of the jugal and dorsal process of the surangular).
Keywords: Pterosauria; anatomy; systematics; Alps; Norian.